199 Takotsubo syndrome associated mir-16 and mir-26a reduce contractility of cardiomyocytes in vitro by an inhibitory g-?protein dependent mechanism. (5th June 2017) - Couch, Liam; A Derda, Anselm; Thum, Thomas; Terracciano, Cesare; Harding, Sian
Abstract : Introduction: Takotsubo syndrome (TTS) is a severe but reversible acute heart failure affecting predominantly post-menopausal women, where ventricular apical akinesis results from extreme adrenaline levels arising with stress. The pleiotropic β²AR signals via stimulatory (Gs ) and inhibitory (Gi ) G-proteins, and whilst Gs increases cardiac output, it concomitantly decreases survival. The duality of β²AR is a homeostatic mechanism to limit cardiotoxicity by facilitating a switch to Gi, serving as cardioprotective despite being cardiodepressive. This is dysregulated in TTS where excess stimulus trafficking to Gi results in profound negative inotropy. It is not understood what predisposes patients to TTS, but a microRNA (miR) profile of increased miR-16 and miR-26a has been identified. Given the importance of miRs in other cardiac diseases and that TTS is thought to be causally related to Î²2AR-Gi, we hypothesise that these miRs could predispose to the cardiodepression in TTS. Method: miRs were manipulated in adult rat apical cardiomyocytes with blinded transfection using Lipofectamine 3000. Percentage shortening was measured using an Ionoptix system, and pharmacological protocols applied. Calcium transients were obtained using Fluo-4-AM and sarcoplasmic reticulum (SR) calcium content measured with caffeine micro-application. N numbers displayed as n/N, where n/N=cells/rats. Results: Up-regulation of miR-16 and miR-26a significantly reduced basal contractility (miR-16=3.520.34% versus control=4.910.46%; n/N=30/6; p<0.05 and miR-26a=2.770.21% versus control=4.300.43%; n/N=50/10; p<0.01), whereas down-regulation had no effect. miR-16/-26a manipulation did not alter β2AR response. Inhibiting Gi with pertussis toxin (PTX) prevented this (miR-16 untreated=5.080.49%, n=22; versus miR-16 PTX-treated=8.820.63%, n=20; p<0.001; and miR-26a untreated=3.200.29% versus miR-26a PTX-treated=5.050.48%; n/N=30/6; p<0.05 respectively). PTX-treatment did not change contractility of control transfected cells. No synergism was observed with dual miR-16/-26a transfection possibly suggesting a unified mechanism. Calcium transient amplitude was decreased with miR-16/-26a up-regulation (F/F0 for control=1.850.04, n/N=66/4 versus miR-16=1.510.04, n/N=37/4 and miR-26a=1.570.04, n/N=26/4; p<0.001), along with a concomitant decrease in SR calcium content (caffeine-induced F/F0 for control=3.130.14, n/N=32/4 versus miR-16=2.130.13, n/N=22/4 and miR-26a=2.570.19, n/N=17/4; p<0.001 and p<0.05 respectively). Conclusion/implication: Increased miR-16/−26a reduce basal contractility of cardiomyocytes in vitro, possibly through a shared Gi -dependent mechanism. Decreased calcium transient amplitude is also likely to contribute. This suggests these miRs may be mechanistically involved in TTS, but further work is needed to investigate their specific mechanistic and spatiotemporal involvement.